Exploring the mechanisms of racialization beyond the black–white binary. Issue 4 (12th March 2019) - Gonzalez-Sobrino, Bianca; Goss, Devon R.
ABSTRACT: Racialization plays a central role in the creation and reproduction of racial meanings, and its inclusion enriches the study of race and ethnicity. While the popularity of the term continues to skyrocket, defining precisely what is meant by racialization can be a daunting task, let alone identifying how, when, where, why, and under what conditions it operates. However, it is essential to recognize the processes of racialization in order to develop a more complete understanding of racial practices, particularly within these increasingly turbulent racial times.